2019
DOI: 10.1111/joms.12441
|View full text |Cite
|
Sign up to set email alerts
|

In and Out of Balance: Industry Relatedness, Learning Capabilities and Post‐Acquisition Innovative Performance

Abstract: The existence of an inverted U‐shaped effect of the relatedness between acquirer and acquired firm on the innovative performance subsequent to an acquisition is normally regarded as indicative of the existence of a trade‐off between exploration and exploitation in external innovation search. We argue that acquirers endowed with heterogeneous learning capabilities can alter the shape of the trade‐off to their favour. In particular, we focus on a notion of industry relatedness that captures the coherence between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 79 publications
2
32
0
1
Order By: Relevance
“…None of the target was acquired in a hostile way. Lim and Lee (2016): transactions with higher degree of relatedness between acquiring and target company lead to more success in cross-border acquisitions Cefis et al (2020): unrelated acquisition can enhance post-acquisition innovative performance up to a certain point (curvilinear inverted -U relationship), but after that point it leads to rigidities Geographical diversification Cross-border acquisitions create more value Danbolt and Maciver (2012): abnormal returns of both targets and bidders are significantly higher in cross-border transactions compared to domestic ones Adnan (2018): international acquirers experience positive returns around the announcement and improve this performance in the post-event period Macroeconomic situation Macroeconomic shocks drive merger waves and influence transaction terms Madura et al (2012): macroeconomic factors (industry growth and capital liquidity) influence demand for target firms and explain the variation in takeover premiums over time Cerrato et al (2016): economic downturn leads to a lower number of non-related and cross-border acquisitions Capital market structure Specifics of capital market cause differences in market reaction to M&A transactions Bagella et al (2005): differences in risk, dividend policies, and expected growth rates influence the investors' sentiment and their expectations to the transaction Martynova and Renneboog (2011): the authors outline the necessity to evaluate separately the UK and Continental Europe transactions due to capital market specifics…”
Section: Data Sample and Methodology Appliedmentioning
confidence: 99%
“…None of the target was acquired in a hostile way. Lim and Lee (2016): transactions with higher degree of relatedness between acquiring and target company lead to more success in cross-border acquisitions Cefis et al (2020): unrelated acquisition can enhance post-acquisition innovative performance up to a certain point (curvilinear inverted -U relationship), but after that point it leads to rigidities Geographical diversification Cross-border acquisitions create more value Danbolt and Maciver (2012): abnormal returns of both targets and bidders are significantly higher in cross-border transactions compared to domestic ones Adnan (2018): international acquirers experience positive returns around the announcement and improve this performance in the post-event period Macroeconomic situation Macroeconomic shocks drive merger waves and influence transaction terms Madura et al (2012): macroeconomic factors (industry growth and capital liquidity) influence demand for target firms and explain the variation in takeover premiums over time Cerrato et al (2016): economic downturn leads to a lower number of non-related and cross-border acquisitions Capital market structure Specifics of capital market cause differences in market reaction to M&A transactions Bagella et al (2005): differences in risk, dividend policies, and expected growth rates influence the investors' sentiment and their expectations to the transaction Martynova and Renneboog (2011): the authors outline the necessity to evaluate separately the UK and Continental Europe transactions due to capital market specifics…”
Section: Data Sample and Methodology Appliedmentioning
confidence: 99%
“…It then requires strong coordination between team members (Marengo et al 2000), which in turn relies upon good communication. By studying post-acquisition innovative performance in relation to R&D investments prior to acquisition for a set of acquisitions, Cefis et al (2020) found that acquiring firms that had nurtured their problem-solving skills and mindset are better able to identify, assimilate, and apply relevant knowledge from the acquired firm. In particular, HEI need to confront with a transformation from a knowledge-importing economy to a knowledge-generating economy.…”
Section: Problem Solvingmentioning
confidence: 99%
“…More specifically, this paper concerns acquisitions conducted to reach high-tech innovations or knowledge, while also addressing the integration of the firm, from non-integration to complete absorption (Haspeslagh and Jemison, 1991; Christensen et al , 2005; Oh and Johnston, 2020; Wei and Clegg, 2020). The literature on acquisitions of innovative firms is frequent to address the difficulties of taking over such firms and maintaining their innovativeness (Lengnick-Hall, 1992; Puranam and Srikanth, 2007; Lamont et al , 2019; Cefis et al , 2020). Indeed, it is even pointed to the difficulties of reaping benefits from innovations already developed at the time of the acquisition (Chaudhuri and Tabrizi, 1999).…”
Section: Theoretical Background and Framingmentioning
confidence: 99%